A collagen-based composite hydrogel and its preparation method and application
By introducing water-soluble lignin and oxidized nanocellulose into the collagen hydrogel and carrying out cross-linking reactions to form a composite hydrogel, the problem of poor mechanical properties of collagen hydrogel is solved, and its biological function and wound healing efficiency are significantly improved.
Patent Information
- Application Number
- CN202311760734.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The existing collagen hydrogels have poor mechanical properties and poor plasticity, and the collagen extracted from traditional animal sources has a risk of poor water solubility and immune rejection.
Collagen-based composite hydrogel is formed by cross-linking reaction in the acetic acid bath by mixing water-soluble lignin with collagen and introducing oxidized nanocellulose.
It improves the mechanical properties and anti-degradation ability of the hydrogel, enhances its antibacterial, antioxidant and anti-inflammatory effects, and significantly improves the efficiency of wound healing.
Smart Images

Figure CN117736466B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel material preparation, and specifically relates to a collagen-based composite hydrogel and a preparation method and application thereof. Background Art
[0002] Collagen is the main component of the extracellular matrix (ECM) of interstitial tissues and is composed of three helical peptide chains entangled with each other. Traditional collagen extracted from animal sources has poor water solubility and may cause immune rejection reactions. Recombinant human collagen (HLC) has attracted widespread attention in the field of tissue engineering due to its good water solubility, low immunogenicity, biocompatibility and biodegradability. However, pure collagen hydrogels have poor mechanical properties and poor plasticity, which limits their application. The mechanical properties and anti-degradation ability of hydrogels can be improved by introducing synthetic polymers and cross-linking them.
[0003] Nanocellulose has the characteristics of high crystallinity, high strength and high specific surface area. The 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO) oxidation system can only oxidize the primary hydroxyl groups of cellulose molecular chain polysaccharides without affecting the secondary hydroxyl groups, effectively improving the dispersibility and interfacial adhesion of nanocellulose in the polymer matrix. Therefore, TEMPO-oxidized nanocellulose (TOCN) can be better dispersed in the composite material, thereby improving the strength and hardness of the composite material.
[0004] Lignin is a phenolic polymer and the second most abundant component in plant cell walls after cellulose. Lignin has many excellent properties, including antibacterial and antioxidant properties, renewability, biodegradability, natural biological activity, and biocompatibility. Based on the various biological functions and cell compatibility of lignin, it has been widely used in the medical field in recent years.
[0005] Wound repair is a complex and orderly biological process, mainly involving hemostasis, inflammation, tissue regeneration and remodeling. Hydrogel is a material with a three-dimensional network structure formed by cross-linking hydrophilic natural or synthetic polymers. It is an ideal wound dressing that can absorb wound secretions, provide breathability and maintain a moist environment for the wound. Collagen is the protein with the highest content in the extracellular matrix. It can attract fibroblasts, promote the formation of new collagen in the wound bed, participate in remodeling and tissue development during wound healing, and interact with various cell surface receptors. Lignin contains a large number of phenolic hydroxyl groups, which can oxidize highly active harmful free radicals into inactive or less reactive oxidative free radicals by breaking OH bonds, donating hydrogen protons and transferring electrons, balancing intracellular reactive oxygen species (ROS) and achieving antioxidant effects. In addition, lignin also has good antibacterial effects. After lignin comes into contact with bacteria, its polyphenol structure will penetrate the cell wall through cleavage, causing the cell membrane to rupture, and then ROS will accumulate on the bacterial surface, effectively inhibiting microbial growth. Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a collagen-based composite hydrogel and its preparation method and application in view of the deficiencies in the prior art.
[0007] In order to solve the above technical problems, the present invention discloses a method for preparing a collagen-based composite hydrogel. The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a collagen-based composite hydrogel, the method is carried out according to the following steps:
[0009] (1) Dissolving water-soluble lignin in water to obtain a lignin aqueous solution.
[0010] (2) Mixing and dissolving the lignin aqueous solution and collagen to obtain a lignin-collagen aqueous solution.
[0011] (3) Mixing the lignin-collagen aqueous solution and the TOCN dispersion to obtain a mixed solution.
[0012] (4) Adjusting the pH of the mixed solution.
[0013] (5) subjecting the mixed solution obtained in step (4) to a cross-linking reaction in an acetic acid bath to obtain a collagen-based composite hydrogel.
[0014] Wherein, in step (1), the water-soluble lignin is prepared as follows: lignocellulose is treated by hydrothermal method to obtain a treatment liquid, the treatment liquid is separated into a filtrate by solid-liquid separation, the filtrate is adsorbed and desorbed by a macroporous adsorption resin, and the desorbed liquid is concentrated and freeze-dried to obtain a water-soluble lignin powder. Preferably, 500 mL of deionized water and 50 g of lignocellulose raw material are treated by hydrothermal method to obtain a treatment liquid. Preferably, the lignocellulose raw material is corn cob. Preferably, the hydrothermal treatment temperature is 170°C and the treatment time is 40 min.
[0015] Preferably, the macroporous adsorption resin is DuPont TM AmberLite TM XAD TM 16N resin, average pore size The resin was soaked in distilled water for 12 hours, fully swollen, the peristaltic pump and adsorption column were adjusted, and 200mL of anhydrous ethanol and 500mL of deionized water were used to pass through the column to activate the resin. 200mL of the filtrate was taken and loaded on the column, and the loading flow rate was 2-16BV / h, and sufficient deionized water was washed, and the washing flow rate was 2-16BV / h. After washing, anhydrous ethanol was used for desorption, and the desorption flow rate was 1-4BV / h. The obtained solution was rotary evaporated to viscosity, the organic solvent was removed, and the water-soluble lignin powder was obtained by freeze drying. The water-soluble lignin structure is connected to low-polymerization polysaccharides by covalent bonds to form a lignin-carbohydrate complex.
[0016] Wherein, in step (1), the water-soluble lignin concentration of the lignin aqueous solution is 3-12 g / L; preferably, the water-soluble lignin concentration is 6 g / L.
[0017] Wherein, in step (2), the collagen is recombinant human collagen. Preferably, the collagen is collagen powder. The added mass of the collagen is 12-20 g per 100 mL of lignin aqueous solution. Preferably, the added mass of the collagen is 18 g per 100 mL of lignin aqueous solution.
[0018] Wherein, in step (2), the lignin water and collagen are mixed and dissolved, preferably by ultrasonic dissolution. The ultrasonic dissolution is preferably ultrasonic dissolution at room temperature for 30 minutes.
[0019] Wherein, in step (3), the TEMPO-oxidized nanocellulose (TOCN) is added in the form of a TOCN dispersion. The TOCN dispersion has a solute concentration of 1% (w / w). Preferably, the preparation method of TOCN [reference Isogai, A., Saito, T., & Fukuzumi, H. (2011). TEMPO-oxidized cellulose nanofibers. Nanoscale, 3 (1), 71–85.], specifically, is as follows: 0.016g TEMPO and 0.1g NaBr are dissolved in 94mL distilled water, 1g hardwood pulp (HBKP) is added, the cellulose content in the hardwood pulp is 40% to 45%, the HBKP is swollen for 20min, 6mL NaClO is added, and the mixture is dissolved by rotation. Then insert the titrator, add 0.5M NaOH and 0.5M HCl to stabilize the pH at 10, add anhydrous ethanol after 4 hours of oxidation to terminate the reaction, use 0.5M HCl to adjust the pH to 3-4, and obtain cotton-like HBKP. Rinse the cotton-like HBKP with distilled water, test whether it has reached neutrality with pH test paper, test the water content, and prepare it into a 0.2% (w / w) TOCN dispersion. The TOCN dispersion is introduced into a homogenizer for homogenization, and then nano-sized with a high-pressure homogenizer, and finally concentrated by rotary evaporation to a concentration of 1% (w / w) TOCN dispersion.
[0020] Wherein, in step (3), the volume ratio of the TOCN dispersion to the lignin-collagen aqueous solution is 1:1-3:1. Preferably, the volume ratio is 2:1-3:1. More preferably, the volume ratio is 2:1.
[0021] Wherein, in step (4), the pH of the mixed solution is adjusted to 4 or 11. Preferably, the pH of the mixed solution is adjusted to 11. The pH of the mixed solution is adjusted using HCl solution and NaOH solution. Preferably, the HCl solution is 0.02M HCl solution; and the NaOH solution is 1M NaOH solution.
[0022] Wherein, in step (4), the cross-linking reaction is carried out at room temperature for 12-24 hours, preferably for 18 hours.
[0023] Preferably, in step (4), the acetic acid bath is an acetic acid solution with a purity of 99.5%.
[0024] The second aspect of the present invention is to provide a collagen-based composite hydrogel prepared by the preparation method.
[0025] The third aspect of the present invention is the use of the collagen-based composite hydrogel in the preparation of wound healing drugs.
[0026] Beneficial effects:
[0027] (1) The present invention proposes a method for preparing a collagen-based composite hydrogel, wherein lignin and nanocellulose, two renewable and degradable plant biomass, are introduced into the collagen-based hydrogel. The prepared composite hydrogel complies with the concept of green and sustainable development.
[0028] (2) The water-soluble lignin prepared by the system of the present invention is structurally connected to the low-polymerization polysaccharide through covalent bonds to form a lignin-carbohydrate complex, in which the free polysaccharide chains enable the water-soluble lignin to attach to the surface of the nanocellulose by intermolecular forces, forming a natural structure similar to that of lignocellulose in nature. Secondly, the antibacterial and antimicrobial effects of lignin (it has the effect of inhibiting the growth and reproduction of both Gram-positive and Gram-negative bacteria), antioxidant and anti-inflammatory effects enhance the effectiveness of the composite hydrogel in wound healing.
[0029] (3) The system of the present invention introduces oxidized nanocellulose into the collagen-based hydrogel, which not only has intermolecular forces (including but not limited to electrostatic forces and hydrogen bonding forces) between the TOCN and the collagen chains, but also the negative charge of the TOCN carboxyl group reacts with the H + The interactions were further cross-linked in an acetic acid bath to form a physical double network structure. The introduction of TOCN improved the poor mechanical properties of collagen itself.
[0030] (4) The rheological mechanical properties of the composite hydrogel prepared by the present invention are controllable. By increasing the amount of oxidized nanocellulose added, the elastic modulus of the composite hydrogel can be greatly improved, and the mechanical properties are excellent.
[0031] (5) The present invention does not require the introduction of any cross-linking agent or toxic reagent during the preparation process, the reaction conditions are mild, the steps are simple, and the natural biocompatibility of collagen is fully retained. It has application prospects in the fields of wound healing and tissue engineering.
[0032] The present invention proposes a preparation method of a collagen-based composite hydrogel, wherein collagen, nanocellulose, and water-soluble lignin form a composite hydrogel in situ. Wherein, oxidized nanocellulose is introduced, and the intermolecular forces between its functional groups and collagen chains (including but not limited to electrostatic forces, hydrogen bonding forces, etc.) can significantly increase the physical crosslinking density of the composite hydrogel, thereby improving its mechanical properties. In addition, water-soluble lignin is introduced to enhance the biological functions of the collagen-based composite hydrogel such as antibacterial and antifungal, anti-oxidation, and anti-inflammatory, and significantly improve the wound healing effect. Secondly, the intermolecular forces (including but not limited to electrostatic forces and hydrogen bonding forces) between nanocellulose, collagen, and water-soluble lignin are physically crosslinked to form a double network structure, which enhances the mechanical properties of the hydrogel, and the system components have good biocompatibility and are non-cytotoxic. Therefore, the hydrogel has excellent effects in wound healing, antibacterial and antifungal, anti-inflammatory, and anti-oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0034] Figure 1 Flow chart of the preparation of collagen-based composite hydrogel.
[0035] Figure 2 This is a picture of the collagen-based composite hydrogel product prepared in Example 4.
[0036] Figure 3 Storage modulus of composite hydrogels cross-linked with TOCN dispersion and HLC / Lignin aqueous solution at different volume ratios under acidic (pH=4) or alkaline (pH=11) conditions.
[0037] Figure 4 Infrared spectra of TOCN, collagen, lignin and composite hydrogel.
[0038] Figure 5 Scanning electron micrograph of the composite hydrogel cross-linked with TOCN dispersion and HLC / Lignin aqueous solution at different volume ratios at pH = 11.
[0039] Figure 6 The inhibition zone diagrams of TOCN / HLC / Lignin mixed solution and HLC / TCON aqueous solution against Bacillus subtilis (a) and Escherichia coli (b). DETAILED DESCRIPTION
[0040] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. The present invention is further described below in conjunction with the accompanying drawings and examples.
[0041] The preparation method of the TOCN dispersion described in the following examples is based on the literature [Isogai, A., Saito, T., &
[0042] Fukuzumi, H. (2011). TEMPO-oxidized cellulose nanofibers. Nanoscale, 3(1), 71–85.] Specifically, 0.016 g TEMPO and 0.1 g NaBr were dissolved in 94 mL distilled water, 1 g hardwood pulp (HBKP) was added, and the cellulose content of the hardwood pulp was 40% to 45%. The HBKP was swollen for 20 min, 6 mL NaClO was added, and the mixture was dissolved by rotation. Then, a titrator was inserted, 0.5 M NaOH and 0.5 M HCl were added to stabilize the pH to 10, and anhydrous ethanol was added after oxidation for 4 h to terminate the reaction. The pH was adjusted to 3-4 with 0.5 M HCl to obtain cotton-like HBKP. The cotton-like HBKP was rinsed with distilled water, and the pH test paper was used to test whether it reached neutrality, and the water content was measured, and it was prepared into a 0.2% (w / w) TOCN dispersion. The TOCN dispersion was introduced into a homogenizer for homogenization, and then nano-formed using a high-pressure homogenizer, and finally concentrated by rotary evaporation to a TOCN dispersion with a concentration of 1% (w / w).
[0043] The preparation method of the water-soluble lignin powder is as follows: 500 mL of deionized water and 50 g of lignocellulose raw material (corn cob) are treated by hydrothermal method to obtain a treatment liquid, the treatment temperature is 170 ° C, the treatment time is 40 min, the treatment liquid is collected, centrifuged and filtered, and the filtrate is taken. Then the macroporous adsorption resin is soaked in distilled water for 12 hours, fully swollen, the peristaltic pump and the adsorption column are adjusted, and 200 mL of anhydrous ethanol and 500 mL of deionized water are passed through the column successively to activate the resin. 200 mL of filtrate is loaded on the column, the loading flow rate is 12 BV / h, and sufficient deionized water is washed, and the washing flow rate is 12 BV / h. After washing, anhydrous ethanol is desorbed, and the desorption flow rate is 4 BV / h. Collect the lignin solution, evaporate it by rotary evaporation until it is viscous, remove the organic solvent, and freeze-dry to obtain the water-soluble lignin powder. The water-soluble lignin structure is connected to low-polymerization polysaccharides by covalent bonds to form a lignin-carbohydrate complex.
[0044] The macroporous adsorption resin is DuPont TM AmberLite TM XAD TM 16N resin, average pore size
[0045] In the following examples, the collagen powder is commercially available recombinant human collagen powder.
[0046] In the following examples, the acetic acid bath is an acetic acid solution with a purity of 99.5%.
[0047] The preparation steps of the collagen-based nanocellulose / lignin composite hydrogel provided by the present invention are as follows: Figure 1 shown.
[0048] Embodiment 1:
[0049] (1) Weigh 0.036 g of water-soluble lignin powder into 3 mL of distilled water and dissolve it at room temperature to obtain a lignin aqueous solution with a water-soluble lignin concentration of 12 g / L.
[0050] (2) Weigh 0.36 g of collagen powder into the lignin aqueous solution, vortex and ultrasonically dissolve it at room temperature for 30 min, that is, the concentration of collagen added to every 100 mL of lignin aqueous solution is 12 g.
[0051] (3) Add 4 mL of 1% (w / w) TOCN dispersion and vortex to mix.
[0052] (4) The pH of the mixed solution was adjusted to 4 using 0.02 M HCl solution.
[0053] (5) Cross-link in an acetic acid bath at room temperature overnight for 12 h.
[0054] Embodiment 2:
[0055] (1) Weigh 0.009 g of water-soluble lignin powder into 3 mL of distilled water and dissolve it at room temperature to obtain a lignin aqueous solution with a water-soluble lignin concentration of 3 g / L.
[0056] (2) Weigh 0.60 g of collagen powder into the lignin aqueous solution, vortex and ultrasonically dissolve it at room temperature for 30 min, that is, the concentration of collagen added to every 100 mL of lignin aqueous solution is 20 g.
[0057] (3) Add 5 mL of 1% (w / w) TOCN dispersion and shake to mix.
[0058] (4) Use 1 M NaOH solution to adjust the pH of the mixed solution to 11.
[0059] (5) Cross-link in an acetic acid bath at room temperature overnight for 16 h.
[0060] Embodiment 3:
[0061] (1) Weigh 0.018 g of water-soluble lignin powder into 3 mL of distilled water and dissolve it at room temperature to obtain a lignin aqueous solution with a water-soluble lignin concentration of 6 g / L.
[0062] (2) Weigh 0.54 g of collagen powder into the lignin aqueous solution, vortex and ultrasonically dissolve it at room temperature for 30 min, that is, the concentration of collagen added to every 100 mL of lignin aqueous solution is 18 g.
[0063] (3) Add 9 mL of 1% (w / w) TOCN dispersion and shake to mix.
[0064] (4) The pH of the mixed solution was adjusted to 4 using 0.02 M HCl solution.
[0065] (5) Cross-link in an acetic acid bath at room temperature overnight for 24 h.
[0066] Embodiment 4:
[0067] (1) Weigh 0.018 g of water-soluble lignin powder into 3 mL of distilled water and dissolve it at room temperature to obtain a lignin aqueous solution with a water-soluble lignin concentration of 6 g / L.
[0068] (2) Weigh 0.54 g of collagen powder into the lignin aqueous solution, vortex and ultrasonically dissolve it at room temperature for 30 min, that is, the concentration of collagen added to every 100 mL of lignin aqueous solution is 18 g.
[0069] (3) Add 6 mL of 1% (w / w) TOCN dispersion and shake to mix.
[0070] (4) Use 1 M NaOH solution to adjust the pH of the mixed solution to 11.
[0071] (5) Cross-link in an acetic acid bath at room temperature overnight for 18 h.
[0072] The composite hydrogel prepared in this example is Figure 2 shown.
[0073] Embodiment 5:
[0074] The composite hydrogel prepared in the above example was characterized by a rheometer, and the storage modulus and loss modulus were recorded. Figure 3 shown. Figure 3 The solid icon in the middle represents the storage modulus, and the hollow icon represents the loss modulus. The storage modulus of the composite hydrogel prepared by the present invention increases with the increase of the TOCN content in the system. When the volume ratio of TOCN to HLC / Lignin solution reaches 2:1 or 3:1, the elastic modulus can be stably maintained above 6000 Pa. Under the same volume ratio conditions, the elastic modulus of the hydrogel cross-linked in an alkaline environment is slightly higher than that of the composite hydrogel cross-linked in an acidic condition.
[0075] The freeze-dried composite hydrogel sample prepared in the above example was characterized by Fourier transform infrared spectrometer, and the infrared spectrum was recorded as follows: Figure 4 See Figure 4 The composite hydrogel contains the characteristic functional groups of collagen, TEMPO-oxidized nanocellulose and lignin, and no new characteristic peaks appear, indicating that no new bonds are generated during the cross-linking process and it is a physical cross-linking.
[0076] The microscopic morphology of the freeze-dried composite hydrogel prepared under alkaline conditions (pH = 11) was observed using a scanning electron microscope. Figure 5 See Figure 5 When the volume ratio of TOCN to HLC / Lignin solution is 5:3, the pore size is relatively closed; when the volume ratio of TOCN to HLC / Lignin solution is 2:1, the porous structure of the composite hydrogel is obvious and the pore size distribution is uniform, and the gaps between the nanofibers become smaller and the combination is tighter; when the volume ratio increases to 3:1, the pore size is too large and unevenly distributed.
[0077] Embodiment 6:
[0078] The agar diffusion method was used to determine the inhibitory effect of lignin in the collagen-based composite hydrogel on Gram-negative bacteria and Gram-positive bacteria (the inhibitory principle is to affect the growth and reproduction of the strain by destroying the cell wall). Among them, Escherichia coli was selected as the test strain for Gram-negative bacteria, and Bacillus subtilis was selected as the test strain for Gram-positive bacteria. Escherichia coli was inoculated in LB liquid medium (10g / L peptone, 5g / L yeast powder, 10g / L NaCl, pH 7.4-7.6), and cultured at 37°C overnight to obtain Escherichia coli culture liquid; Bacillus subtilis was inoculated in Bacillus subtilis liquid medium (3g / L KH2PO4, 0.5g / L MgSO4, 5g / L sucrose, 15g / L peptone, 30mL / L corn steep liquor, pH 5.0-5.5), and cultured at 37°C overnight to obtain Bacillus subtilis culture liquid. Take 0.1mL of a concentration of 1.0×10 6 CFU / mL of Escherichia coli and Bacillus subtilis were spread on LB solid plates (10g / L peptone, 5g / L yeast powder, 10g / L NaCl, 20g / L agar) and Bacillus subtilis solid plates (1g / L KH2PO4, 0.5g / L MgSO4, 10g / L peptone, 10mL / L corn steep liquor, 20g / L agar), respectively. Three 6mm circular holes were punched at equal distances on the nutrient agar plate using a hole puncher. 100μL of the HLC / TOCN / Lignin mixed solution described in Example 4 and the HLC / TOCN aqueous solution with the same volume ratio as that in Example 4 were added to each circular hole, and sterile water was used as a control. After overnight culture at 37°C, the size of the inhibition zone was observed. The antibacterial effect of lignin was evaluated using the diameter of the inhibition zone as an indicator. Figure 6a. The diameter of the inhibition zone of the HLC / TOCN / Lignin mixed solution containing lignin on Bacillus subtilis was measured to be 14.00 mm (20.00 mm-6.00 mm=14.00 mm), while the HLC / TOCN solution had no obvious inhibition zone on Bacillus subtilis. Judging from the size of the inhibition zone, lignin has a strong antibacterial effect on Bacillus subtilis [References: Yan Yarong, Gao Yamin, Liao Juan, etc. Study on the inhibitory effect of Zanthoxylum bungeanum leaf extract on Escherichia coli and Staphylococcus aureus [J]. Smart Agriculture Guide, 2022, 2(22): 37-39+42.]. Figure 6 As shown in Figure b, the diameter of the inhibition zone of the HLC / TOCN / Lignin mixed solution on E. coli is 5.00 mm (11.00 mm-6.00 mm=5.00 mm), while the HLC / TOCN solution has no obvious inhibition zone on E. coli. Judging from the size of the inhibition zone, lignin has a weaker antibacterial effect on E. coli. Therefore, using corn cobs as raw materials, the extracted lignin has a specific antibacterial effect on both Gram-positive and Gram-negative bacteria, among which the antibacterial effect on Gram-positive bacteria is more prominent. This may be due to the large difference between the cell walls of Gram-positive bacteria and Gram-negative bacteria, and lignin is more likely to affect the cell walls of Gram-positive bacteria, thereby inhibiting the growth and reproduction of strains.
[0079] The present invention provides a method for preparing a collagen-based composite hydrogel and a method and idea for its application. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a collagen-based composite hydrogel, characterized in that: The following steps are involved: (1) dissolving water-soluble lignin in water to obtain a lignin aqueous solution; the water-soluble lignin is prepared by the following method: treating lignocellulose by a hydrothermal method to obtain a treated solution, separating the treated solution into a filtrate by solid-liquid separation, adsorbing and desorbing the filtrate by a macroporous adsorption resin, and concentrating and freeze-drying the desorbed solution to obtain a water-soluble lignin powder; (2) mixing and dissolving the lignin aqueous solution and collagen to obtain a lignin-collagen aqueous solution; (3) mixing the lignin-collagen aqueous solution with TOCN to obtain a mixed solution, wherein the TOCN refers to TEMPO-oxidized nanocellulose; (4) adjusting the pH of the mixed solution to 4 or 11; (5) subjecting the mixed solution obtained in step (4) to a cross-linking reaction in an acetic acid bath to obtain a collagen-based composite hydrogel.
2. The preparation method according to claim 1, characterized in that: In step (1), the lignin aqueous solution has a water-soluble lignin concentration of 3-12 g / L.
3. The preparation method according to claim 1, characterized in that: In step (2), the collagen is recombinant human collagen; the added mass of the collagen is 12-20 g per 100 mL of the lignin aqueous solution.
4. The preparation method according to claim 1, characterized in that: In step (3), the TOCN is added in the form of a TOCN dispersion; the TOCN dispersion has a solute concentration of 1% w / w.
5. The preparation method according to claim 4, characterized in that: In step (3), the volume ratio of the TOCN dispersion to the lignin-collagen aqueous solution is 1:1-3:
1.
6. The preparation method according to claim 1, characterized in that: In step (5), the cross-linking reaction is carried out at room temperature for 12-24 hours.
7. The collagen-based composite hydrogel prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the collagen-based composite hydrogel according to claim 7 in the preparation of wound healing drugs.
Citation Information
Patent Citations
Preparation method of oxidized nano-cellulose / collagen composite sponge
CN105079886A
Nanometer cellulose-salicylic aldehyde thiosemicarbazone-polyvinyl alcohol hydrogel fluorescence probe, and preparation method and applications thereof
CN109824918A